Agents and data mining interaction 8th International Workshop, ADMI 2012, Valencia, Spain, June 4-5, 2012, Revised Selected Papers - Cao, Longbing; Zeng, Yifeng; Symeonidis, Andreas L.; Gorodetsky, Vladimir I.; Yu, Philip S.; Singh, Munindar P. (Lecture Notes in Computer Science, 2013)
This book constitutes the thoroughly refereed post-workshop proceedings of the 8th International Workshop on Agents and Data Mining Interaction, ADMI 2012, held in Valencia, Spain, in June 2012. The 16 revised full papers were carefully reviewed and selected from numerous submissions. The papers are organized in topical sections on agents for data mining, data mining for agents, and agent mining applications.